High-efficiency biodegradation of crude oil and p-hydroxybenzoic acid by Acinetobacter haemolyticus JS-1: Integrated characterization and genomic analysis - Weiyi Tao; Jijie Lu; Junzhang Lin; Mingshan Ding; Weidong Wang; Shuang Li (Ecotoxicology and Environmental Safety)
Crude oil contamination is a major threat to both the environment and human health. Acinetobacter haemolyticus strain JS-1 was isolated from oil-contaminated soil in Jiangsu Oilfield, China, which exhibits exceptional biodegradation capabilities for crude oil and p-hydroxybenzoic acid (PHBA). This strain can degrade 70–80 % of crude oil at concentrations of 10–20 g/L within 15 days at 30 °C. Strain JS-1 does not produce surfactants but absorbs crude oil through cell surface hydrophobicity. RT-qPCR analysis has identified five types of alkane hydroxylase genes in strain JS-1, including two AlkB-types, one AlmA-type, one LadA-type, and a cytochrome P450 monooxygenase. These genes are likely contributed to its high degradation efficiency. Notably, the CYP153 enzyme is crucial for metabolizing hexadecane and octadecane. We further investigated the PHBA degradation pathway, revealing both the protocatechuate ortho-cleavage pathway and a potential ubiquinone biosynthesis pathway. The remarkable efficiency of strain JS-1 in crude oil biodegradation positions it as a promising candidate for mitigating crude oil pollution. Moreover, its effective PHBA degradation provides new opportunities for the application of microorganism in agricultural management.